2019
DOI: 10.1101/580530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Presynaptic boutons that contain mitochondria are more stable

Abstract: 10Addition and removal of presynaptic terminals reconfigures neuronal circuits of the 11 mammalian neocortex, but little is known about how this presynaptic structural plasticity is 12 controlled. Since mitochondria can regulate presynaptic function, we investigated whether the 13 Figure 1 -Tracking bouton plasticity and mitochondrial positioning in axons of motor cortex 1 neurons. (A) AAV expressing cytosolic EGFP and a mitochondrial targeting sequence (MTS) 2 conjugated to TagRFP was injected in to M1/M2 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…We thank Lilly UK for the gift of the AAV used in this study. This manuscript has been released as a preprint in BioRxiv (Lees et al, 2019).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We thank Lilly UK for the gift of the AAV used in this study. This manuscript has been released as a preprint in BioRxiv (Lees et al, 2019).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Some recent research (Smit-Rigter et al 2016; Lees et al 2020) suggest that in vivo mitochondria may stay in the stationary state for longer periods of time than in vitro . The model parameters can be adjusted to characterize transitions between anterograde, retrograde, and stationary states.…”
Section: Resultsmentioning
confidence: 99%
“…High mitochondrial proportions also facilitate synaptic transmission through rapid vesicle turnover including their mobilization from reserve pools upon repetitive/intense stimulation (Vos, Lauwers, & Verstreken, ) and through effective buffering and sequestering of calcium (Billups & Forsythe, ; Devine & Kittler, ). High mitochondrial proportions were present in MGm boutons of all sizes indicating that even smaller boutons may have a higher impact on postsynapses and are more stable (Lees, Johnson, & Ashby, ) than other cortical boutons of comparable size. Other studies have shown that layer IV thalamocortical boutons are also relatively rich in mitochondria (mitochondrial fraction: 0.21; Kharazia & Weinberg, ) and were, in contrast to layer II boutons, considered as “drivers” (Viaene, Petrof, & Sherman, ).…”
Section: Discussionmentioning
confidence: 98%